Penerapan Perawatan Selang Gastrointestinal Untuk Mencegah Risiko Infeksi Pada Tn “R” Dengan Ileus Obstruktif Di Ruang Walet Rumah Sakit Bhayangkara Makassar - Firmansyah; Lala; Nadia Selviati Herman (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
Obstructive ileus is a digestive surgical emergency caused by a disruption in the flow of intestinal contents that cannot pass through the gastrointestinal tract. The WHO records intestinal obstruction as a leading cause of morbidity and mortality, with nearly 30,000 deaths per year. At Bhayangkara Hospital Makassar in 2023, there were 180 cases of obstructive ileus, with 109 patients hospitalized (0.12%) and 71 patients receiving outpatient care (0.9%). The main concern in obstructive ileus is the risk of infection due to suboptimal care, which can lead to necrosis or damage to the gastrostomy tract. This study employs a case study design to explore the application of gastrointestinal tube care in patient Mr. "R," who experienced pain, heat, and redness around the nose due to the placement of a gastrointestinal tube. Gastrointestinal tube care intervention proved effective in preventing the risk of infection. Following nursing interventions, symptoms decreased, with the pain scale reducing from 5 (moderate) to 3 (mild). These results indicate that proper care can reduce the risk of complications and enhance patient comfort in cases of obstructive ileus.